Optimizing Energy Output for Oscillating Water Column (OWC) Wave Energy Converter System at Pantai Baron, Gunung Kidul, DI Yogyakarta - Kurniawan, Aries Taufiq; Budiman, Arief; Budiarto, Rachmawan; Prasetyo, Ridwan Budi (ASCEE, 2024)
The prototypes of the Oscillating Water Column (OWC) system constructed by BPPT at Pantai Baron, Gunung Kidul, in 2005 and 2006 were not sustainable. Based on its condition and location, the root cause of the problem was defined. Maximizing the total efficiency and capacity factor (Cf) of the OWC system was the main factor for optimizing energy output. Collecting factors that constructed the total efficiency and capacity factor of the OWC system was conducted. Selecting the appropriate turbine, generator, and chamber system led to an increase in the total efficiency of the OWC system. Reducing the effect of wave diffraction, finding optimum wave data for forecasting, finding optimum water depth area to avoid wave breaking area, reducing corrosion chance by selecting the optimum height of the OWC system, and using a control system to minimize stalling on turbine were factors that constructed capacity factor